(untitled) (Gumilyov Journal of Pedagogy, 2026)
This scientific article presents an in-depth analysis of pre-service primary school teachers’ professional perceptions of international educational assessment programs such as TIMSS and PIRLS, utilizing structural modeling. The study employed the SmartPLS software to analyze quantitative data and assess the nature of pre-service teachers’ attitudes and professional interpretations of these evaluation systems. TIMSS (Trends in International Mathematics and Science Study) and PIRLS (Progress in International Reading Literacy Study) are comprehensive international assessments that evaluate the quality of education and are regarded as key indicators of reform efforts and teaching quality improvements in modern education systems. Therefore, the perceptions of future teachers regarding these assessments serve as an important criterion for evaluating their level of professional preparedness. The research was conducted among third- and fourth-year students majoring in "Pedagogy and Methods of Primary Education" at Korkyt Ata Kyzylorda University. Empirical data were collected using a structured questionnaire. The content of the questionnaire was grouped into five thematic blocks comprising 25 indicators. The collected data were analyzed using the PLS-SEM (Partial Least Squares Structural Equation Modeling) methodology, and statistical processing was carried out through measurement and structural models. The analysis revealed that future teachers perceive TIMSS and PIRLS not only as mechanisms for comparing student achievement but also as valuable methodological resources that can be integrated into pedagogical practice. The results of the study aim to improve teacher training systems in higher education institutions, foster professional competencies, and develop strategies for adapting to international assessment systems. Furthermore, the findings are intended to contribute scientifically and practically to the modernization of the national educational content and its alignment with global standards.